A Novel Method to Purposely Modify the Anode/Electrolyte Interface in Solid Oxide Fuel Cells. Issue 47 (17th December 2019) - Zhao, Jie; Xu, Xiaoyong; Zhou, Wei; Zhu, Zhonghua; Guo, Yu; Zhong, Shenglai
Abstract: A novel method is proposed to modify the Ni‐yttria stabilized zirconia (YSZ) anode/electrolyte interface with Ni‐Sm0.2 Ce0.8 O2‐δ (SDC) or SDC composite particles. Scanning electron microscopy results confirm that nano‐sized NiO‐SDC particles are only loaded at the anode/electrolyte interface rather than the whole NiO‐YSZ support. With the addition of the Ni‐SDC composite, the peak power density of the Ni‐YSZ anode increases by 24.7% and 18.8% in wet hydrogen and methane at 750 °C, respectively. Electrochemical impedance spectroscopy results show that these improvements are attributed to the promotion of charge transfer and gas diffusion with the addition of the Ni‐SDC composite. Substituting the Ni‐SDC composite with pure SDC can further improve the electroactivity of the Ni‐YSZ anode. The peak power density of the single cell with the Ni‐YSZ/SDC anode rises by 41.7% and 43.4% compared with that of the Ni‐YSZ anode in wet hydrogen and methane at 750 °C, respectively. Abstract : Clever approach: Sm0.2 Ce0.8 O2‐δ (SDC) nanoparticles are scattered over Ni‐yttria stabilized zirconia (YSZ) composite particles at the anode/electrolyte interface of a Ni‐YSZ anode‐supported solid oxide fuel cell. The peak power densities of the cell increase by 41.7% and 43.4% with the addition of SDC nanoparticles in hydrogen and methane at 750 °C, respectively.